1977
DOI: 10.1042/bj1640685
|View full text |Cite
|
Sign up to set email alerts
|

Selective permeability of rat liver mitochondria to purified aspartate aminotransferases in vitro

Abstract: 1. A method was devised to allow determination of intramitochondrial aspartate amino-transferase activity in suspensions of intact mitochondria. 2. Addition of purified rat liver mitochondrial aspartate aminotransferase to suspensions of rat liver mitochondria caused an apparent increase in the intramitochondrial enzyme activity. No increase was observed when the mitochondria were preincubated with the purified cytoplasmic isoenzyme. 3. These results suggest that mitochondrial aspartate aminotransferase, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Both proteins fall within the typical range of polarities (47 6 %) for soluble proteins with the mitochondrial isozyme being marginally less polar (44.6 % compared with 45.6%); this small difference is abolished if the amino acids cysteine and tyrosine are included among the polar residues (polarities of 49.5 and 49.6 for the cytosolic and mitochondrial isozymes respectively). A lower value for the polarity of the mitochondrial isozyme might have been expected given that it must be transported through the mitochondrial membrane system from its site of synthesis in the cytosol to its site of action in the mitochondrial matrix [8,9]; this expectation is clearly not realised in practice. Alternatively, the mitochondrial isozyme may possess a region of low polarity on its surface involved in recognition and transport through the membrane system, without this being apparent from the overall polarity.…”
Section: Compuv Ison Of the Overall Amino Acid Compositionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Both proteins fall within the typical range of polarities (47 6 %) for soluble proteins with the mitochondrial isozyme being marginally less polar (44.6 % compared with 45.6%); this small difference is abolished if the amino acids cysteine and tyrosine are included among the polar residues (polarities of 49.5 and 49.6 for the cytosolic and mitochondrial isozymes respectively). A lower value for the polarity of the mitochondrial isozyme might have been expected given that it must be transported through the mitochondrial membrane system from its site of synthesis in the cytosol to its site of action in the mitochondrial matrix [8,9]; this expectation is clearly not realised in practice. Alternatively, the mitochondrial isozyme may possess a region of low polarity on its surface involved in recognition and transport through the membrane system, without this being apparent from the overall polarity.…”
Section: Compuv Ison Of the Overall Amino Acid Compositionsmentioning
confidence: 96%
“…This last-mentioned aspect is of particular interest since it has recently been demonstrated [8,9] that intact rat liver mitochondria are permeable to the native mitochondrial isozyme but not to the cytosolic form. This selective permeability may be the basis for the unique intracellular localisation of the isozymes [3] and work is in progress to account for the selectivity in molecular terms; it has already been shown that modification of a single exposed sulphydryl group abolishes uptake of the mitochondrial isozyme into mitochondria [lo].…”
mentioning
confidence: 99%
“…On the contrary significant differences have been found for the cytosolic isozymes from ox [4], pig [5,6] and chicken heart [25]. As mitochondrial isozymes are synthesized in the cytosol [26], of very much interest appear to be studies concerning the transport mechanism [27] which could be responsible for the observed evolutionary constraints concerning the structure of mitochondrial aspartate aminotransferases.…”
Section: Enzyme Crystallization and X-ray Studiesmentioning
confidence: 99%
“…Briefly, RH LV M, suspended in 2 ml of a standard medium in the presence of 2 μg rotenone and 1 mM sodium arsenite, were incubated with aspartate (12 mM) and, after 1 min, ·-oxoglutarate was added to a final concentration of 3 mM. The rate of decrease of fluorescence was then recorded and taken as a measurement of intramitochondrial AAT activity (24).…”
Section: Isolation Of Mitochondriamentioning
confidence: 99%
“…The method measures the intramitochondrial activity of aspartate aminotransferase and uses a Perkin-Elmer LS5 spectrofluorometer. The details of the assay method and the conditions under which it provides a true measurement of intramitochondrial enzyme activity have been reported (24). Briefly, RH LV M, suspended in 2 ml of a standard medium in the presence of 2 μg rotenone and 1 mM sodium arsenite, were incubated with aspartate (12 mM) and, after 1 min, ·-oxoglutarate was added to a final concentration of 3 mM.…”
Section: Isolation Of Mitochondriamentioning
confidence: 99%